Condicionamiento clásico y cognición implícita (2006)
Experimental data, behavioral and psychobiological, reviewed in this paper show that human classical conditioning has an evolutionary purpose, it is developed by means of a cognitive processing different from the conscious processing, and sustained by different cerebral structures. These structures usually do not work isolated. For that reason, combination of both forms of processing, explicit/implicit, is the general pattern in natural conditions. In fact, due to the hierarchical organization of the nervous system, usually it exists a top-down control process (cortical-subcortical) but, under special conditions of laboratory, can be behaviorally evident, for example by means of the fear conditioning, close relationship between implicit processing and Pavlovian conditioning in humans.